FORMING OF RESPONSIBILITY IN CHILDREN OF OLDER PRE-SCHOOL AGE BY MEANS OF FICTION LITERATURE - Chepil, Maria; Karpenko, Oresta; Dudnyk, Nadia; Revt, Alla; Svyontyk, Oleksandra (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2023)
A civilized society sets requirements for the democratic coexistence of persons who possess moral values, benefit society and develop their own abilities. An important characteristic of a person is responsibility, which is formed as a result of the integration of thought processes, social norms, personal attitude in solving dilemmas in life. Responsibility as a child’s conscious behavior in relation to people and nature begins to develop in the period of older preschool age. Independent thinking in judgments acquires logic and a personal attitude to reality. In the pursuit of social activity, children imitate the behavior of significant adults, heroes of their favorite films, cartoons, and works of art. Educators and parents are faced with the task of developing the philosophy of children's worldview through conducting moral and ethical discussions. Our survey of children’ parents with special needs showed a low level of parents’ and educators’ attention to the education of responsibility (4%) compared to other personal qualities (discipline ‑ 18%, ability to adapt to life ‑ 20%, respect to parents ‑ 14%, etc.). This indicates the need to conduct special educational activities that compensate for gaps in value orientations. Emphasis has also been shifted in the education of executive responsibility as opposed to initiative responsibility (75% : 25%), which gives reasons to look for new ways in organizing the interaction of participants in the educational process, to use moral and ethical conversations, to study educational children's literature, in particular, the works of V. Sukhomlynskyi (2018), which became the goal of our scientific exploration. Examples of artistic works and developed problematic questions and tasks for educational work with children of older preschool age in the conditions of a preschool education institution are given.